Adaptation and psychometric evaluation of the breastfeeding self-efficacy scale to assess exclusive breastfeeding: a cross-sectional study in rural China - Linhua Li; Zhengjie Cai; Xinru Zhou; Jieyuan Feng; Chang Sun; Yuju Wu; Scott Rozelle; Huan Zhou (BMC, 2024)
Abstract Background Despite the benefits of exclusive breastfeeding, the proportion of exclusively breastfed children remains low in rural China. Self-efficacy is one of the most crucial modifiable factors predicting breastfeeding behavior. However, existing instruments in China do not specifically measure self-efficacy for exclusive breastfeeding but rather measure self-efficacy for any breastfeeding. Furthermore, they have been validated only in high-income Chinese settings. We sought to adapt and validate an instrument to measure exclusive breastfeeding self-efficacy within rural Chinese contexts. Methods We introduced relevant items to Dennis' Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF), which can assess maternal self-efficacy for exclusive breastfeeding. It was then implemented in a multistage random cluster sampling design and cross-sectional survey with home-visit interviews among women 0-6 months postpartum (n = 654) in the rural areas of four counties in Sichuan, China. We performed item-total and adjusted item-total correlations, as well as exploratory factor analysis to remove redundant items and determine the latent factor structure. We further applied confirmatory factor analysis to test the dimensionality of the scale. We then assessed the reliability of the scale and conducted tests of predictive and divergent validity. Known group comparisons were made by primiparous status and breastfeeding support level. We compared the validated Exclusive Breastfeeding Self-Efficacy Scale with the BSES-SF in terms of reliability and validity to explore the added value of scale modification. Results Our modification of the BSES-SF to target exclusive breastfeeding produced 19 items. This was further reduced to 15 items based on adjusted item-total correlations and exploratory factor analysis, forming the Exclusive Breastfeeding Self-Efficacy Scale. This scale had three dimensions: "Breast milk supply and quality," "Breastfeeding skills," and "Exclusive breastfeeding" subscales. The Exclusive Breastfeeding Self-Efficacy Scale demonstrated strong internal consistency and overall reliability with a Cronbach's alpha coefficient of 0.91. Predictive and divergent validity and known group comparison assessments supported its validity. Robust psychometric evaluations demonstrated enhanced validity and reliability compared to the original BSES-SF. Conclusions Our Exclusive Breastfeeding Self-Efficacy Scale is valid and reliable for measuring exclusive breastfeeding self-efficacy within rural Chinese contexts and is ready for adaptation and validation for clinical and programmatic use elsewhere, particularly within LMICs.